Caracterização agronômica e molecular da coleção nuclear de arroz da Embrapa - BUENO, Luíce Gomes (2010)
The plant genetic resources stored ex situ are considered as a genetic repository, and are raw material for the development of the world agriculture. In rice, despite its high genetic variability, the lack of information of accessions to compose a databank prevents its use to help the choice of genitors for the breeding programs. The Embrapa Rice Core Collection (ERiCC) was developed from 10,000 accessions from Embrapa GeneBank, and it was set up by 550 accessions, divided in three subsets: 1) 94 lines and cultivars from Brazil (LCB); 2) 148 lines and cultivars from abroad (LCI); and 3) 308 traditional varieties (VT), obtained from germplasm collection expeditions in Brazil. This work aimed: 1) to evaluate the extension of genetic variability of 550 accessions from ERiCC by means of agronomic traits characterization using mixed models and multivariate statistics; 2) to perform a comparative analysis of the genetic divergence considering the agronomical and SSR markers characterizations; and 3) to identify the genotypes with higher genetic diversity and with the best agronomic performances, aiming to promote the most efficient use of such germplasm in breeding programs. The agronomic characterization of 550 accessions was performed in nine field experiments, evaluating 18 phenological-agronomic traits. The data were analyzed using the mixed linear and AMMI models. There was wide variation range of genotypical values for most evaluated traits. In different environments, it was observed VT accessions among the high-yielding materials, demonstrating the potential of this group of germplasm, particularly important due to its high genetic variability, to contribute to the development of cultivars regionally adapted. The AMMI approach allowed a good discrimination of ERiCC rice genotypes in relation to the adaptive performance, identifying the accessions CA880078, CA990001, CA870071 (subset VT), and CNA0009113 (LCI) as having good yield and broad adaptation to distinct environments. The comparative analysis of genetic diversity between agronomic and molecular data was performed using the 242 lines and cultivars accessions from ERiCC, which were characterized by 86 fluorescent SSR markers, and five agronomic traits with genotypic values predicted (values without from the effects of interaction genotypes x environment, from a joint analysis of nine experiments. The genetic divergence among accessions was estimated by the average Euclidian distance for phenotypical data, and by the Rogers modified by Wright (RW) genetic distance. The datasets were jointly analyzed by descriptive and multivariate statistics, using correlation analyses from hierarchical grouping of Ward and UPGMA methods. The phenotypical and molecular data showed a broad distribution of dissimilarity indexes, despite they showed different patterns of variation between them. Low molecular distances were associated to low phenotypical distances, however to high molecular distances, occurred a high broad range of phenotypical variation. The correlation between genetical and phenotypical dissimilarities was significant for both lowland and upland accessions, despite with different values (r=0.156 and r=0.409, respectively). Due to the low relation between phenotypical and molecular data, the analysis of genotypes to be used in breeding programs must include both evaluations to a better accession characterization. Considering the high yielding accessions, the higher molecular distances were identified among the accessions from lowland system of cultivation, among which BR IRGA 413 and CNA0005014, BR IRGA 413 and CNA0005853, and CNA0004552 and CNA0005014. Considering the upland accessions, maximum genetic distances were identified in CNA0000482 and CNA0006422, CNA0001006 and CNA0006422, and CNA0001006 and CNA0003490. The molecular analysis was able to identify accessions with reduced genetic relationship, that if used as genitors, will result in a progeny with a high probability to find new allelic combinations. On the other hand, the phenotypical characterization is important to identify accessions not just genetically divergent, but with superior agronomic trait performances for breeding programs. The results of this work will permit to increase the activities related to the characterization of accessions from rice Genebank, giving support of breeding programs to choose the best accessions to obtain new cultivars, with favorable traits, and broad genetic basis. In addition, a continuous program of phenotypical and molecular characterization of germplasm will be able to identify accessions to increase the genetic variability of ERiCC.